Gut Microbiota, Obesity and Metabolic Dysfunction - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2011)
BACKGROUND: The prevalence of obesity and related disorders such as metabolic syndrome and diabetes has vastly increased throughout the world. Recent insights have generated an entirely new perspective suggesting that our microbiota might be involved in the development of these disorders. This represents an area of scientific need, opportunity and challenge. The insights gleaned should help to address several pressing global health problems.CONTENT: Our bowels have two major roles: the digestion and absorption of nutrients and the maintenance of a barrier against the external environment. They fulfill these functions in the context of, and with the help from, tens of trillions of resident microbes, known as the gut microbiota. Studies have demonstrated that obesity and metabolic syndrome may be associated with profound microbiotal changes, and the induction of a metabolic syndrome phenotype through fecal transplants corroborates the important role of the microbiota in this disease. Dietary composition and caloric intake appear to swiftly regulate intestinal microbial composition and function.SUMMARY: The interaction of the intestinal microbial world with its host, and its mutual regulation, will become one of the important topics of biomedical research and will provide us with further insights at the interface of microbiota, metabolism, metabolic syndrome, and obesity. A better understanding of the interaction between certain diets and the human gut microbiome should help to develop new guidelines for feeding humans at various time points in their life, help to improve global human health, and establish ways to prevent or treat various food-related diseases.KEYWORDS: gut microbiota, obesity, metabolic syndrome, type 2 diabetes